2022
DOI: 10.1039/d1ob02316k
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of cage-opened C60 derivatives mediated by frustrated Lewis pairs

Abstract: Multiply-carbonylated fullerene derivatives were found to work as one component in frustrated Lewis pairs which caused an Si–H bond activation in the presence of B(C6F5)3, leading to the carbonyl hydrogenation in up to 99% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…In 2018, we demonstrated a high‐yielding triple reduction via the Luche conditions employing NaBH 4 with CeCl 3 [9] . We also found that even weak/mild reductants, such as BH 3 ⋅THF [10] and Frustrated Lewis pairs using B(C 6 F 5 ) 3 and HSiPh 3 , [11] work for reducing a carbonyl group on the C 60 orifice to generate a hydroxy stopper.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, we demonstrated a high‐yielding triple reduction via the Luche conditions employing NaBH 4 with CeCl 3 [9] . We also found that even weak/mild reductants, such as BH 3 ⋅THF [10] and Frustrated Lewis pairs using B(C 6 F 5 ) 3 and HSiPh 3 , [11] work for reducing a carbonyl group on the C 60 orifice to generate a hydroxy stopper.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the two signals were determined to be 99.67:0.33 which is in accordance with the natural abundance of 14 N (I = 1) and 15 N (I = 1/2). 16 Thus, the former signal broadening is caused by the rapid quadrupolar relaxation of 14 NH 3 while it is absent in the 15 N isotopologue showing a coupling constant of J NH = 60.1 Hz. 17 From full width at half-maximum ν 1/2 of the proton resonance, the transverse relaxation time of 14 NH 3 was estimated to be T 2 = 7.8 ms which is rather shorter than that of H 2 16 O (0.27 s) where the protons relax with a spin− rotation mechanism.…”
mentioning
confidence: 96%
“…The enol form of B then underwent hydrolysis to give quinone and NH 3 together with C which changes into D and 4 via disproportionation. 10,14 Notably, phenanthrenequinone is known to undergo a unique self-condensation reaction to give an isoimide derivative in the presence of ammonium acetate. 15 Thus, we anticipated that the formation of quinone and NH 3 is a driving force to afford imidazole-containing πextended fullerenes 3 (Figure 2c).…”
mentioning
confidence: 99%